2003
DOI: 10.1258/135763303321159620
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing for orthopaedic outpatients: one-year follow-up

Abstract: We studied whether consultations via videoconferencing and traditional outpatient clinic visits differ in terms of the implementation of the patient management plan during a one-year follow-up. First-admission and follow-up orthopaedic patients were randomly allocated to an outpatient visit at the surgical department of Oulu University Hospital or to videoconferencing at a health centre in Pyhäjärvi. In a prospective one-year study, there were 145 consecutive orthopaedic patients who met the inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 7 publications
(11 reference statements)
1
70
0
2
Order By: Relevance
“…We did not find any significant difference between the two groups concerning referral to operation, regardless of whether the planned operations were performed or not. This was also the case when the analysis was restricted to the new referred patients (data not presented), which is in conjunction with the findings of another follow-up study on videoconferencing with orthopaedic outpatients [9]. …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We did not find any significant difference between the two groups concerning referral to operation, regardless of whether the planned operations were performed or not. This was also the case when the analysis was restricted to the new referred patients (data not presented), which is in conjunction with the findings of another follow-up study on videoconferencing with orthopaedic outpatients [9]. …”
Section: Discussionsupporting
confidence: 69%
“…Another RCT evaluated patients coming to an emergency department and found telemedicine to be a satisfactory treatment technique [5]. Others suggest that telemedicine is an alternative to conventional visits for orthopaedic patients in an outpatient setting [69]. In one study, real-time videoconference was found to suitably provide orthopaedic care to rural areas; however, further investigations, including a cost–benefit analysis, were recommended [10].…”
Section: Introductionmentioning
confidence: 99%
“…Others have investigated remote orthopaedic consultations by various means (videoconference [18][19][20][21][22] , Skype 23 , or teleconference 24 ) and reported cost-savings and similar clinical outcomes compared with in-clinic assessments. Although those alternative methods may achieve savings in some circumstances, the webbased system for routine arthroplasty follow-up provides greater flexibility to complete the assessment at a time and location *The values are given as the mean and the standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…a GP, a general surgeon or a resident) have been present at the remote site together with the patient [8,10,11,34,35]. Some studies reported that a nurse present at the remote site and a specialist at the hospital could provide satisfactory remote consultations in emergency medicine [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Today, the use of telemedicine to facilitate treatment and care over distance has been investigated in almost all clinical specialties [5][6][7]. Several studies have demonstrated the feasibility of using telemedicine to provide orthopaedic consultations to patients living in remote areas [8][9][10][11]. Teleorthopaedics involve the delivery of specialist services across a distance, usually between an orthopaedic surgeon and a patient [12].…”
Section: Introductionmentioning
confidence: 99%